Social Media Addiction and Adolescent Mental Health: The Mediating Role of Cognitive Interference in Digital Communication - Sharma, Kavita; Gera, Manju (WISE Pendidikan Indonesia, 2025)
This study investigates the relationships among social media addiction, cognitive interference, and mental health outcomes within the context of digital communication among adolescents aged 13–19 in Chandigarh, India. Utilizing a cross-sectional design, data were collected from 541 participants who completed the Bergen Social Media Addiction Scale (BSMAS), a computerized Stroop Test to assess cognitive interference, and the Depression, Anxiety, and Stress Scale (DASS-21). Results indicated moderately high levels of social media addiction (M = 4.2, SD = 1.1), substantial cognitive interference (incongruent trials: M = 850 ms), and moderate psychological distress across all mental health indicators. Correlation analyses revealed that social media addiction was positively associated with cognitive interference (r = 0.45, p < 0.01) and negatively associated with mental health outcomes (r = -0.38, p < 0.01). Cognitive interference was also significantly and negatively correlated with mental health (r = -0.42, p < 0.01), indicating that increased cognitive disruption due to digital engagement exacerbates emotional distress. Mediation analysis confirmed that cognitive interference partially mediated the relationship between social media addiction and mental health, accounting for approximately 35% of the total effect. These findings underscore cognitive interference as a critical psychological mechanism linking problematic social media use to adverse mental health outcomes among adolescents. The study contributes region-specific empirical evidence to the global discourse on digital media effects and highlights the urgency of implementing targeted interventions such as cognitive training and digital literacy programs to mitigate the cognitive and emotional risks associated with excessive digital communication in adolescent populations.